The facilitation of constructional meaning in the processing of Mandarin innovative Bei construction - Liao, Qiaoyun; Weng, Xin; Dong, Chao; Zhang, Yuxin (Frontiers in Psychology, 2023)
The processing of Mandarin innovative Bei construction in the form of “Bei + X”, such as “被和谐 (“be harmonied”, a person’s opinions that are at odds with prevalent views held in society are either silenced or edited)”, is different from that of the traditional Bei construction in that the former activates the emergent constructional meaning (Goldberg, 1995, 2006, 2019) of “Bei + X” which is intrinsically negative. This study investigated whether the processing mechanism of Mandarin innovative Bei construction is facilitated by the access of its emergent negative constructional meaning by conducting a self-paced reading experiment. Participants read three types of lexical primes including construction-related phrases (i.e. phrases expressing the negative constructional meaning of the innovative Bei construction), component-related phrases (i.e. phrases expressing the partial literal meaning of the innovative Bei construction), and unrelated phrases (i.e. phrases expressing unrelated meaning to the innovative Bei construction). Then they read materials containing the innovative Bei construction as well as answering questions by pressing the “space” key. Results showed that the lexical primes conveying the constructional meaning of the innovative Bei construction significantly shortened participants’ reading time durations as compared with another two priming conditions. To conclude, the processing of Mandarin innovative Bei construction is facilitated by the priming of its constructional meaning, which provides some new psychological evidence for the construction-based processing mechanism of Mandarin innovative Bei construction.